It is all up to me - Razpotnik, Špela (Teorija in praksa, 2011)
Today's young people are considered the most educated generation ever, yet their (employment) perspectives are uncertain, the job market is open to them yet offers changed conditions that every day seem to be more exploitative. The transitions of young people to work have in the past decades become prolonged, diversified, unstable and uncertain. In the course of destandardisation such transitions have become fragmented. Inequality has also changed in terms of its forms of reproduction and consequences. Success or failure in education are increasingly ascribed to individual decisions and performance in line with the individual responsibility discourse. Even in these new circumstances, education is still a key factor in reproducing structures of social inequality. The article explores dimensions of inequality reproduced by the education system, especially the role of social status and ethnicity. These dimensions (and their intersections) are placed in opposition to the idea of individual responsibility that seems to be an explanation of inequalities in educational success, transitions or access according to all of the reference groups included in the presented research (students, parents, teachers and other school experts).
Keywords: prehod iz šole na delo; transition from school to work; youth; mladina; social inequality; socialna neenakost; družbena neenakost; education; izobraževanje; odgovornost